Using genetic inference to re-evaluate the minimum longevity of the lemon shark Negaprion brevirostris - Brooks, J.; Guttridge, T.; Franks, B.; Grubbs, R.; Chapman, D.; Gruber, S.; Di Battista, Joseph; Feldheim, K. (Wiley-Blackwell Publishing Ltd., 2016)
A combination of mark-recapture and genetic sampling was used to extend the minimum longevity of an elasmobranch species and the life span estimate of the lemon shark Negaprion brevirostris was increased conservatively from 20·2 to 37 years. This increase in longevity means higher vulnerability and a longer recovery time from exploitation.